2013
DOI: 10.2105/ajph.2012.300983
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Health Care Use Associated With Community Coalitions: Long-Term Results of the Allies Against Asthma Initiative

Abstract: Mobilizing a diverse group of stakeholders, and focusing on policy and system changes generated significant reductions in health care use for asthma in vulnerable communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 8 publications
1
29
1
Order By: Relevance
“…11 Community coalitions provide a basis for developing and enacting changes in community health and health policy. 1 However, great ideas do not necessarily translate into great actions; movement from thinking about to enacting change can be conceptualized via movement through five stages (precontemplation, contemplation, preparation, action, and maintenance 14 ). ἀe current article represents a unique addition to literature on coalitions and change processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Community coalitions provide a basis for developing and enacting changes in community health and health policy. 1 However, great ideas do not necessarily translate into great actions; movement from thinking about to enacting change can be conceptualized via movement through five stages (precontemplation, contemplation, preparation, action, and maintenance 14 ). ἀe current article represents a unique addition to literature on coalitions and change processes.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the workgroup described in this article are all participants in the Bayou La Batre coalition, which drew primarily from agencies operating in and around Mobile (Alabama). Consistent with its mission (and other successful coalitions 1 ), the GS-HPC coalition included multiple stakeholders with well-rounded expertise, including members from county and state health departments, nonprofits, faith-based groups, schools and universities, health organizations, city and county government, social clubs, the extension system, wellness groups, business groups, chambers of commerce, and regional planning commissions. Members brought a range of skills, knowledge, and experience to the GS-HPC coalition, and represented organizations focused on a variety of health and socioeconomic issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This national program supported by the Robert Wood Johnson Foundation, has been described in detail in previous publications [15,16]. Evaluation of the Allies coalitions demonstrated that such collective effort can bring about significant policy and system change related to clinical care and management of asthma and that in a cohort of asthma patients followed over one year, significant symptom reduction was evident [15].…”
Section: Introductionmentioning
confidence: 97%
“…Evaluation of the Allies coalitions demonstrated that such collective effort can bring about significant policy and system change related to clinical care and management of asthma and that in a cohort of asthma patients followed over one year, significant symptom reduction was evident [15]. Further, using Medicaid data, the Allies study showed that improved asthma outcomes were community wide, that is, an enhanced health status of the population of low income children residing in target communities [16].…”
Section: Introductionmentioning
confidence: 99%